2017
DOI: 10.1007/s41742-017-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Co-digestion of the Energy Crop Sida hermaphrodita and Microalgae Biomass for Enhanced Biogas Production

Abstract: This study presents the results of anaerobic codigestion of perennial crop Sida hermaphrodita and microalgae biomass under semi-continuous conditions. The aim of this study was to compare biogas potential from the silage of Sida mixed in different ratios with microalgal species of Chlorella sp. and Scenedesmus sp. The results showed that the co-digestion process improved biogas/ methane production to the level of 594.52/351.88 mL/g volatile solids. The best results were achieved when microalgae biomass constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…However, when silage made from Sida biomass was mixed with microalgal species, the amount of biogas and methane produced reached 595 and 352 mL g −1 volatile solids. When microalgae biomass comprised 40 and 60 % of the substrate, the highest gas yields were obtained (Dębowski et al ., ).…”
Section: The Use Of Sida As Biofuel: Biophysical and Biochemical Propmentioning
confidence: 97%
“…However, when silage made from Sida biomass was mixed with microalgal species, the amount of biogas and methane produced reached 595 and 352 mL g −1 volatile solids. When microalgae biomass comprised 40 and 60 % of the substrate, the highest gas yields were obtained (Dębowski et al ., ).…”
Section: The Use Of Sida As Biofuel: Biophysical and Biochemical Propmentioning
confidence: 97%
“…Some studies have focussed on improving the biogas and methane yield by mixing S. hermaphrodita with other biomass. Dębowski et al [150] mixed S. hermaphrodita silage and microalgae (Chlorella sp. and Scenedesmus sp.)…”
Section: Growing Sida Hermaphrodita and Silphium Perfoliatum As Solidmentioning
confidence: 99%
“…The highest methane yields are typically achieved by having two harvests rather than one harvest per year [17]. The application of pre-treatments can increase methane yields, but they incur additional energy costs [138,148,150]. For example, Kisielewska et al [149] concluded that the increase in biogas and methane yields after ultrasound pre-treatments could not be justified from an energy balance perspective.…”
Section: Energy Balances and Lcasmentioning
confidence: 99%
“…Biomass energy has been recognised as one of the options that will play an important role in future energy scenarios, and a recently emerging strategy is to convert biomass into clean energy fuels via biorefinery technology [3]. Currently, biorefineries are mainly based on energy crops, however, the main concern in using energy crops for the bioenergy market is that their production on agricultural land may detrimentally affect global food supplies [4]. Compared to energy crops, using microalgae for biofuel production has become an alternative in order to reduce competition with the food industry.…”
Section: Introductionmentioning
confidence: 99%